2020
DOI: 10.2298/tsci200409286d
|View full text |Cite
|
Sign up to set email alerts
|

Excess heat utilization combined with thermal storage integration in district heating systems using renewables

Abstract: District heating systems already play an important role in increasing the sustainability of the heating sector and decreasing its environmental impact. However, a high share of these systems is old and inefficient and therefore needs to change towards the 4th generation district heating, which will incorporate various energy sources, including renewables and excess heat of different origins. Especially excess heat from industrial and service sector facilities is an interesting source since it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…TIMES [46,76] has been extensively modified to suit the specific requirements of various regions and has high flexibility, while Balmorel [117] has been modified in a few studies and is assigned to have medium to high flexibility. Oemof [108][109][110][111] has also been modified to create different versions of the tool in several previous studies to suit the requirements. Although no literature has been found on the flexibility of Calliope, several additions and changes have been made to enhance the functionality of the tool [141].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMES [46,76] has been extensively modified to suit the specific requirements of various regions and has high flexibility, while Balmorel [117] has been modified in a few studies and is assigned to have medium to high flexibility. Oemof [108][109][110][111] has also been modified to create different versions of the tool in several previous studies to suit the requirements. Although no literature has been found on the flexibility of Calliope, several additions and changes have been made to enhance the functionality of the tool [141].…”
Section: Discussionmentioning
confidence: 99%
“…Andersen et al used EnergyPRO to compare different policies for providing support schemes to increase flexibility in DHCS [110]. Doračić et al modelled the utilization of EH combined with the implementation of thermal energy storage in a DHS [111]. The availability of EH was modelled at an hourly resolution to account for its variability.…”
Section: Energypromentioning
confidence: 99%
“…First of all, the available excess heat from the refinery has been calculated by combining the Heat Roadmap Europe method presented in [37] and the maximum available excess heat potential from chemical industry in Croatia presented in [12], giving the maximum availability of this source 10.3 GWh. Its availability has not been assumed constant but variable (Figure A 3) , by applying the variation presented in the previous research of the authors [18], while the temperature level has been assumed high enough for the direct utilization through the heat exchanger. Service sector excess heat facilities have been added to the analysis to also consider the low temperature excess heat sources, which need a heat pump to increase the temperature level to the required district heating supply temperature.…”
Section: Scenariosmentioning
confidence: 99%
“…Through the previous research of the authors, mainly Refs. [17] and [18], it has been concluded that the main competitors of excess heat sources in terms of feasibility are low cost technologies like solar thermal. Furthermore, there is a plan in development to include solar district heating into the system in Sisak in the near future.…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation